2016
DOI: 10.1002/cctc.201600331
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol to 1,3‐Butadiene Conversion by using ZrZn‐Containing MgO/SiO2 Systems Prepared by Co‐precipitation and Effect of Catalyst Acidity Modification

Abstract: Abstract:The conversion of ethanol to 1,3-butadiene (1,3-BD) has been investigated over ZrO2 and ZnO containing magnesia silica oxides prepared by co-precipitation method at different Mg-to-Si molar ratios. The effect of reaction temperature and ethanol flow rate was investigated. The catalyst acidity was modified through the addition of alkali metals (Na, K and Li) to the final materials. Catalysts were characterised by nitrogen physisorption analysis, Xray diffraction, scanning electron microscopy with energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
72
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 48 publications
(196 reference statements)
6
72
0
Order By: Relevance
“…One issue is the difference in preparation method which significantly alters many of the features of the MgO-SiO 2 catalysts, making their comparison difficult, as evidenced by the different Mg-to-Si ratios being reported as optimal. In general, it is recognizes that a predominantly basic catalyst with some degree of acidity is the preferred balance to produce active materials [7,13,25,27,29,30,51]. Weckhuysen et al have reported that sufficient amount of Lewis acid in the form of Mg-O-Si with small amounts of strong basic sites has led to the most active wet-kneaded catalysts [51].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One issue is the difference in preparation method which significantly alters many of the features of the MgO-SiO 2 catalysts, making their comparison difficult, as evidenced by the different Mg-to-Si ratios being reported as optimal. In general, it is recognizes that a predominantly basic catalyst with some degree of acidity is the preferred balance to produce active materials [7,13,25,27,29,30,51]. Weckhuysen et al have reported that sufficient amount of Lewis acid in the form of Mg-O-Si with small amounts of strong basic sites has led to the most active wet-kneaded catalysts [51].…”
Section: Discussionmentioning
confidence: 99%
“…Rather than tweaking the preparation method, the acid properties of a catalyst can be altered by a post-treatment with alkali metals [30,33,60]. Both Jones et al and Wang et al have reported the selective poisoning of the stronger acid sites on their zirconium-containing catalysts [30,33].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations